Genetic Identification of Parasitic Giardia enterica in Three Wild Rodent Species from a Zoological Institution: First Host Records in Brazilian Porcupine (Coendou prehensilis) and Naked Mole Rat (Heterocephalus glaber), and Detection in Crested Porcupine (Hystrix cristata) - Lorena Esteban-Sánchez; Marta Mateo-Barrientos; Manuel de la Riva-Fraga; Lino Pérez de Quadros; Juan José García Rodríguez; Francisco Ponce-Gordo (Journal of Zoological and Botanical Gardens, 2025)
Flagellates of the genus Giardia are intestinal parasites with a broad host range. Several Giardia duodenalis variants (assemblages) recently elevated to species rank—G. duodenalis (assemblage A1), G. intestinalis (A2) and Giardia enterica (B) are human pathogens. Giardia enterica has been reported in some hystricomorph rodents such as wild crested porcupines (Hystrix cristata), but no data were previously available from Brazilian porcupines (Coendou prehensilis) and naked mole rats (Heterocephalus glaber). The aim of this study is to genetically identify the Giardia isolates from these three rodent species, all housed in a zoological institution. Fecal samples were processed using the Bailenger concentration method, and DNA was extracted from the sediments using commercial kits. Partial PCR amplification and sequencing of the glutamate dehydrogenase, beta-giardin, and triose-phosphate isomerase genes revealed that all isolates belonged to G. enterica, showing 99–100% identity with sequences available in GenBank. Prevalences could not be reliably estimated due to small group sizes and the resulting proportions may be biased. To our knowledge, this is the first report identifying Giardia (G. enterica) in C. prehensilis and H. glaber, thus expanding the known host range of this parasite species and reinforcing the importance of surveillance in captive wild hosts.